The Relationship of Self-Concept with The Level of Anxiety in Mothers during Menopause in The Ciceri District Health Center - Fathiyati, Fathiyati (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Menopause is a period when female reproduction ends due to a reduction in the hormones estrogen and progesterone which is marked by the cessation of menstruation. During menopause, physical and psychological changes occur which cause changes in self-image (body image). This change creates stress in itself for menopausal mothers. If the mother cannot adapt, this stressful condition will cause anxiety. This descriptive correlation research aims to identify the self-image of mothers during menopause, the level of anxiety of mothers during menopause, and the relationship between self-image and the level of anxiety of mothers during menopause. The respondents were 32 menopausal mothers who live in Ciceri Village. The data collection process was carried out by filling out a questionnaire using the interview method. The correlation test used is Pearson's product moment r. The results showed that there was a significant positive correlation between self-image and maternal anxiety levels during menopause (r = 0.39; p = 0.02) with the interpretation of a moderate relationship. From the results of this study it can be concluded that there is a significant relationship between self-image and the level of anxiety of mothers during menopause. Therefore, special attention is needed for menopausal mothers, not only on physical problems, but also psychological problems. Health education is needed for menopausal mothers, and so that mothers can accept gracefully that menopause is a natural process that all women will go through, adapting to all conditions that occur during menopause, so that anxiety can be avoided